2014
DOI: 10.1136/bcr-2014-206016
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of pulmonary tuberculosis and sarcoidosis: a diagnostic dilemma

Abstract: Tuberculosis and sarcoidosis are multisystem diseases having different aetiology and management; however, they have similar clinical and histological characteristics. Very rarely they may coexist. We report a rare case of a 38-year-old woman who presented with chronic cough, low-grade fever and respiratory distress that was initially diagnosed as miliary tuberculosis. Diagnosis was supported by positive mycobacterial culture and initially responded to antitubercular treatment, but later recurrences led to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It is notable that there was detection of inhA in 59% of the subjects with sarcoidosis, suggesting that the use of isoniazid would be a potential therapeutic agent in these subjects, serving as the backbone of latent and active tuberculosis therapy. Sarcoidosis and tuberculosis can coexist within the same host (22)(23)(24)(25). Interestingly, studies have demonstrated the appearance of sarcoidosis after completion of tuberculosis therapy (26,27) However, the ability to detect DNA encoding potential targets of antimicrobials does not ensure that such antimicrobials would be active against the bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that there was detection of inhA in 59% of the subjects with sarcoidosis, suggesting that the use of isoniazid would be a potential therapeutic agent in these subjects, serving as the backbone of latent and active tuberculosis therapy. Sarcoidosis and tuberculosis can coexist within the same host (22)(23)(24)(25). Interestingly, studies have demonstrated the appearance of sarcoidosis after completion of tuberculosis therapy (26,27) However, the ability to detect DNA encoding potential targets of antimicrobials does not ensure that such antimicrobials would be active against the bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed clinical history and histologic correlation are therefore essential for differentiating tuberculous myocarditis from sarcoidosis. It has also been observed as reported in previous studies that both sarcoidosis and TB can coexist, 19 20 causing diagnostic dilemma and the presence of both disease conditions in the same patient does not exclude each other and need to considered. At the time of writing this case report, antitubercular treatment had been initiated and the importance of follow-up imaging has been explained to monitor treatment response.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, some studies have suggested that patients with TB or SA should be further divided into four subtypes: sarcoidosis (SA), sarcoid-tuberculous (ST), tuberculous-sarcoid (TS), and tuberculosis (TB) (Agrawal et al, 2016;Mandal et al, 2014). This classification method implies that MTB may also exist in patients with SA and indicates a great risk of dissemination of TB lesions after hormone treatment.…”
Section: Discussionmentioning
confidence: 99%